2007
DOI: 10.1111/j.1399-0039.2006.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype association of IL‐8 gene with Behcet’s disease

Abstract: Interleukin-8 (IL-8), a CXC chemokine that recruits and activates inflammatory cells, plays a critical role in the pathogenesis of Behcet's disease (BD). To investigate the association of the genetic polymorphism of IL-8 and BD, we genotyped IL-8 -845 T/C, -738 T/A, -353 A/T, -251 A/T, +293 G/T, +678 T/C and receptors CXCR-1 +2607 G/C and CXCR-2 +785 C/T polymorphisms in 119 Korean patients with BD and 119 age- and sex-matched healthy blood donors. Then, single nucleotide polymorphisms (SNPs) and haplotypes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used to genotype the IL-8 −845 T/C, −738 T/A, −251 A/T and +781 C/T polymorphisms in patients and controls, as described elsewhere [22,27]. All the subjects' genotypes were analyzed blinded.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used to genotype the IL-8 −845 T/C, −738 T/A, −251 A/T and +781 C/T polymorphisms in patients and controls, as described elsewhere [22,27]. All the subjects' genotypes were analyzed blinded.…”
Section: Genotypingmentioning
confidence: 99%
“…Recently, relationship between IL-8 SNPs and haplotypes and some autoimmune diseases has also been reported [22][23][24]. As OLP is a kind of disease which correlate with autoimmune reaction [1][2], we hypothesized that SNPs and haplotypes of IL-8 gene might be associated with the susceptibility of individuals to OLP, as well as the progression and prognosis of this disease.…”
Section: Introductionmentioning
confidence: 97%
“…There are more than 70 IL-8 gene polymorphisms known to be associated with several pathologies (44,46,47,50,78), but as yet, there are no studies associating the -353 A/T polymorphism in IL-8 with dengue, despite the evidence of its involvement in the pathogenesis of infection (7,9,16,40,62). The A allele of the -353 A/T polymorphism in IL-8 has been correlated with higher IL-8 production in comparison with the T allele (34), but no study has been able to show associations when analyzing this polymorphism individually, suggesting that the combined effect of several IL-8 polymorphisms is necessary (45,47,50).…”
mentioning
confidence: 99%
“…These findings indicate that additional genetic risks remain to be discovered. Many approaches to searching for genetic risk have been used to identify additional risk loci for BD, such as genome‐wide linkage scans in multiplex families (14) and candidate gene association studies (15–33). Recently, genome‐wide association studies (GWAS) for BD have identified several risk loci at IL23R – IL12RB2 , IL10 , KIAA1529 , CPVL , LOC100129342 , UBASH3B , and UBAC2 in Turkish and Japanese patients (34–36).…”
mentioning
confidence: 99%